“O estudante prepara-se para reagir nas batalhas do porvir”: escritos nos jornais estudantis secundaristas em Aracaju/SE (1874-1915) - Santos, Luana de Jesus (2024)
This dissertation focuses on the student newspapers O Porvir (1874), O Necydalus (1909- 1911) and O Atheneu (1915), all linked to the Atheneu Sergipense located in the city of Aracaju/SE. The general objective of this research is to analyze the writings of high school students in student newspapers from the late 19th and early 20th centuries. To this end, the following specific objectives were outlined: a) Discuss the materiality of student newspapers in the proposed time frame; b) Discuss the themes covered in the student publications in focus; c) Investigate the traces of school material culture conveyed in students’ writings. Within this perspective, these writings dialogue with the concepts of school culture (Escolano Benito, 2017) and representation (Chartier, 1990, 2002). The similarity of the forms under analysis points to the most recurrent themes in discussions about public education (primary and secondary), about school rituals (graduations, exams, competitions, writing practices) as well as about topics such as science and religion. The practice of writing, the production and circulation of printed materials present aspects of the “empirical culture of the school”, the objects on display, the rituals, the interaction and experiences expressed elucidate a scenario of training for high school students. In view of the analysis of secondary school publications from Aracaju, it is clear that the representation of students' writings marked a scenario of battles for the improvement of secondary education in Sergipe, the enthusiasm deposited by teachers, editors and other subjects, culminating in the formation of intellectuality of Sergipe people who took flight, thus overcoming the ignorance caused by the lack of education.